PHOSPHORUS RECOVERY FROM WASTEWATER BY HYDROTALCITE AND ZEOLITE - Y. Mishima; H. Araki (Lowland Technology International, 2010)
A system using hydrotalcite and zeolite is developed for the recovery of phosphorus from wastewater having low phospate concetrations. As HT and Ze is independently used, redundant ion species are produced in a desorbing solution. As HT and Ze are used in combination, however, the opposite redundant ion species can be used to desorb PO43- and NH4+, respectively. Simply alkaline NaCl solution is used to desorb/regenerate HT/Ze. Moreover, desorbed substances can be recovered as magnesium ammonium phosphate (MAP) by the addition of Mg. In this paper, the desorption of PO43- and NH4+ from HT and Ze into a single desorbing solution and phosphorus recovery from the desorbing solutions as MAP are experimentally investigated. It is verified that the single desorbing solution can simultaneously desorb HT and Ze. Whereas 95% of phosphate was recovered from the desorbing soluition in which PO43- and NH4+ were accumulated, most of the recovered phosphorus was not MAP but Mg3(PO4)2 (MP). However, when the initial concentrations of PO43- and NH4+ in the desorbing solution increased, MAP was procuded rather easily and more than 90% of P was recovered. Further investigation into application for the practical plant is necessary.